A cidade como suporte artístico: visões poéticas materializadas em obras de projeção mapeada urbana - Pereira, Edgar Roberto Luiz (2014)
In this dissertation, we defined Urban Projection Mapping as a study object. This is an expressive form through which audiovisual artists projectover city structures poetic images that represent their views in relation to the environment in which they live. We present the literature that served as our theoretical boundary of urban space, specifically the social space of contemporary Western metropolis. The concepts developed by Italian architect and theorist Aldo Rossi, together with definitions of social space and spaces of representation developed by French philosopher Henri Lefebvre, as well as Cultural Studies author understandings of culture and representation, and considerations about artistic support by Milton Sogabe constitute our theoretical framework to understand the city as an artistic medium. Following, we present the Urban Projection Mapping as a specific art form and cultural phenomenon, noting some uses we observed inthe artistic practice mediated by technological devices. We propose to articulate the historical and cultural processes that have enabled the consolidation of Urban Projection Mapping as an expressive format after exposing our understanding of the term "articulation", seen as both theory and method. The articulations between the Projection Mapping and contemporary art, according to Arthur Danto and Hans Belting perceptions, and aligned to the investigation of contemporary art's phenomena called happening, site-specific art and urban art, as well asthe VJing activity, constitute the historical context of the historic-cultural environment in which our subject belongs. Finally, we explore the poetic universe in some specific works of Urban Projection Mappingin Brazil and overseas, in wich the city is a temporary support that artists map, in terms of physical and symbolic conditions, and transform in their materialized view,making contradictions visible, displacing meanings and establishing new points of view in relation to the territory we inhabit.